Flat cross-section glass fiber, glass fiber reinforced resin composition, and glass fiber reinforced resin molded product

By using flat-section glass fibers of specific cross-sectional shapes and sizes, the problems of the oval cross-sectional glass fibers having many breakages, poor spinning properties and severe cutting edge wear in the spinning and chopped wire production process are solved, and excellent spinning properties and chopped wire productivity are achieved.

CN118715186BActive Publication Date: 2025-04-01NITTO BOSEKI CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380017739.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-26
Publication Date
2025-04-01
Estimated Expiration
2043-01-26

AI Technical Summary

Technical Problem

Oval cross-section glass fiber has problems such as frequent breakage, poor spinning properties and severe cutting edge wear during spinning and chopped wire production, resulting in low productivity.

Method used

Flat cross-sectional glass fibers with specific cross-sectional shapes and sizes are used, and the length of the cross-sectional diameter is in the range of 15.0 to 25.0 μm, the short diameter is in the range of 8.0 to 12.0 μm, the special shape ratio R is in the range of 1.5 to 3.0, the filling rate P is in the range of 80.1 to 89.9%, and the specific ratio conditions are met to improve spinning properties and chopped wire productivity.

Benefits of technology

By using such flat cross-section glass fiber, it is possible to significantly improve spinning properties and chopped wire productivity while maintaining the same dimensional stability and tensile strength, reduce the number of tool replacements, and improve production efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a flat cross-section glass fiber that can obtain excellent spinnability and short-cut raw yarn productivity compared with an oblong cross-section glass fiber. The present invention relates to the following glass fiber: it comprises a plurality of flat cross-section glass filaments with a flat cross-sectional shape, the cross-sectional major diameter of the flat cross-section glass filament is 15.0 to 25.0 μm, the minor diameter is 8.0 to 12.0 μm, the ratio of the major diameter to the minor diameter (major diameter / minor diameter), i.e., the profile ratio R, is 1.5 to 3.0, the ratio of the cross-sectional area of ​​the flat cross-section glass filament to the area of ​​a rectangle circumscribed to the cross-sectional area of ​​the flat cross-section glass filament, i.e., the filling rate P, is in the range of 80.1 to 89.9%, and the profile ratio R and the filling rate P satisfy the following formula (1): 337.6≤P 3 / 2 / R≤421.2…(1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to flat cross-section glass fibers, glass fiber reinforced resin compositions and glass fiber reinforced resin molded products. Background Art

[0002] In the prior art, there is known a glass fiber reinforced resin molded product containing glass fibers (hereinafter sometimes referred to as flat cross-section glass fibers) containing a plurality of flat cross-section glass filaments having a flat cross-section (for example, see Patent Document 1).

[0003] In particular, a glass fiber reinforced resin molded article containing the following glass fiber (hereinafter, sometimes referred to as oblong cross-section glass fiber) suppresses the occurrence of warping compared to a glass fiber reinforced resin molded article containing a plurality of glass filaments having a circular cross-section (hereinafter, sometimes referred to as circular cross-section glass fiber), and thus has excellent dimensional stability and excellent mechanical properties such as tensile strength, and can therefore be used in thin and short accessories such as portable electronic device housings. The oblong cross-section glass fiber contains a plurality of flat cross-section glass filaments (hereinafter, sometimes referred to as oblong cross-section glass filaments) having an oblong cross-section shape (a shape in which the short sides of a rectangle are replaced with semicircles having the short sides as diameters).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2020 / 137004 Summary of the invention

[0007] Problems to be solved by the invention

[0008] However, compared with circular cross-sectional glass fibers, oblong cross-sectional glass fibers have a disadvantage in that the number of filament breakages during spinning is greater and the spinnability is inferior.

[0009] Moreover, when the oblong cross-sectional glass fiber (glass strand) comprising a plurality of oblong cross-sectional glass filaments is cut into a predetermined length and processed into chopped strands, the cutting blade is easily worn compared to the case of using the circular cross-sectional glass fiber, and the number of times the cutting blade is replaced increases, resulting in an undesirable situation in which the productivity of the chopped strands is poor.

[0010] The object of the present invention is to provide a flat cross-section glass fiber, which can maintain the same mechanical properties such as dimensional stability and tensile strength when made into a glass fiber reinforced resin molded product compared with the above-mentioned oblong cross-section glass fiber, and eliminate the above-mentioned undesirable conditions, and can obtain excellent spinnability and short-cut strand productivity compared with the oblong cross-section glass fiber.

[0011] Means for solving problems

[0012] In order to achieve the above-mentioned object, the glass fiber of the present invention is characterized in that it comprises a plurality of flat cross-sectional glass filaments having a flat cross-sectional shape, the major diameter of the cross-section of the flat cross-sectional glass filament is in the range of 15.0 to 25.0 μm, the minor diameter is in the range of 8.0 to 12.0 μm, the ratio of the major diameter to the minor diameter (major diameter / minor diameter), i.e., the profile ratio R, is in the range of 1.5 to 3.0, the ratio of the cross-sectional area of ​​the flat cross-sectional glass filament to the area of ​​a rectangle circumscribed to the cross-sectional area of ​​the flat cross-sectional glass filament (cross-sectional area of ​​the flat cross-sectional glass filament / area of ​​a rectangle circumscribed to the cross-sectional area of ​​the flat cross-sectional glass filament), i.e., the filling rate P, is in the range of 80.1 to 89.9%, and the profile ratio R and the filling rate P satisfy the following formula (1):

[0013] 337.6≤P 3 / 2 / R≤421.2…(1).

[0014] In addition, the flat cross-section glass fiber of the present invention preferably has the above-mentioned profile ratio R and the above-mentioned filling rate P satisfying the following formula (2):

[0015] 361.9≤P 3 / 2 / R≤382.5…(2).

[0016] Furthermore, the glass fiber reinforced resin composition of the present invention is characterized in that the flat cross-section glass fiber of the present invention is contained in the resin composition.

[0017] Furthermore, the glass fiber reinforced resin molded article of the present invention is characterized by being composed of the glass fiber reinforced resin composition of the present invention.

[0018] According to the flat cross-section glass fiber of the present invention, in which the profile ratio R and the filling rate P satisfy the formula (1), the glass fiber reinforced molded product of the present invention can maintain the same mechanical properties such as dimensional stability and tensile strength as the glass fiber reinforced resin molded product containing the oblong cross-section glass fiber, and can obtain excellent spinnability and excellent chopped strand productivity compared to the oblong cross-section glass fiber.

[0019] Here, being able to maintain the same dimensional stability compared to a glass fiber reinforced resin molded product containing oblong cross-section glass fibers means that the warpage of the glass fiber reinforced resin molded product measured by the measuring method described later is less than 10.0 mm. In addition, being able to maintain the same mechanical properties compared to a glass fiber reinforced resin molded product containing oblong cross-section glass fibers means that the tensile strength measured by the measuring method described later is more than 230 MPa.

[0020] In addition, being able to obtain excellent spinnability means that the number of spinning breaks measured by the measurement method described below is less than 10 times. In addition, being able to obtain excellent chopped strand productivity means that the number of tool replacements measured by the measurement method described below is less than 30 times.

[0021] In addition, by making the above-mentioned profile ratio R and the above-mentioned filling rate P of the flat cross-section glass fiber of the present invention satisfy the above-mentioned formula (2), the glass fiber reinforced molded product of the present invention can obtain excellent mechanical properties such as dimensional stability and tensile strength compared with the glass fiber reinforced resin molded product containing oblong cross-section glass fiber, and the flat cross-section glass fiber of the present invention can obtain better spinnability and better short-cut strand productivity than the oblong cross-section glass fiber.

[0022] Here, compared with the fiber-reinforced resin molded product containing oblong cross-section glass fibers, being able to obtain excellent dimensional stability means that the warpage of the glass-reinforced resin molded product measured by the method described later is less than 7.5 mm. In addition, compared with the fiber-reinforced resin molded product containing oblong cross-section glass fibers, being able to obtain excellent mechanical properties means that the tensile strength measured by the method described later is more than 240 MPa.

[0023] Further, being able to obtain more excellent spinnability means that the number of spinning breaks measured by the method described below is less than 9. Further, being able to obtain more excellent chopped strand productivity means that the number of blade replacements measured by the method described below is less than 20.

[0024] Furthermore, the glass fiber reinforced resin molded article of the present invention can maintain the same mechanical properties such as dimensional stability and tensile strength as those of a glass fiber reinforced resin molded article containing oblong cross-section glass fibers.

[0025] Here, maintaining the same mechanical properties such as dimensional stability and tensile strength as those of a glass fiber-reinforced resin molded product containing oblong cross-sectional glass fibers has the same meaning as described above. DETAILED DESCRIPTION

[0026] Next, embodiments of the present invention will be described in further detail.

[0027] The flat cross-section glass fiber of the present embodiment comprises a plurality of flat cross-section glass filaments having a flat cross-section shape, wherein the cross-section of the flat cross-section glass filament has a major diameter in the range of 15.0 to 25.0 μm, a minor diameter in the range of 8.0 to 12.0 μm, and an irregularity ratio R in the range of 1.5 to 3.0, and has a flat cross-section shape. Here, the cross-section of the flat cross-section glass filament refers to a cross-section perpendicular to the length direction of the flat cross-section glass filament, and the irregularity ratio R is the ratio of the major diameter to the minor diameter (major diameter / minor diameter).

[0028] In addition, the filling rate P of the flat cross-section glass fiber of the present embodiment is in the range of 80.1 to 89.9%, and the above-mentioned profile ratio R and the above-mentioned filling rate P satisfy the following formula (1), and preferably satisfy the following formula (2).

[0029] 337.6≤P 3 / 2 / R≤421.2…(1)

[0030] 361.9≤P 3 / 2 / R≤382.5…(2)

[0031] Here, the filling rate P is the ratio of the cross-sectional area of ​​the flat cross-sectional glass filament to the area of ​​the rectangle circumscribing the cross-sectional area of ​​the flat cross-sectional glass filament (cross-sectional area of ​​the flat cross-sectional glass filament / area of ​​the rectangle circumscribing the cross-sectional area of ​​the flat cross-sectional glass filament).

[0032] For example, the flat cross-section glass fiber of the present embodiment can be manufactured by the following method. First, a glass raw material (batch glass material) prepared into a specified glass composition is supplied to a melting furnace, and the glass raw material is melted at a temperature in the range of, for example, 1450 to 1550°C. Next, when the molten glass batch material (molten glass) is pulled out from 10 to 30,000 nozzle heads of a sleeve controlled to have a specified temperature and quenched, the nozzle heads are set to a non-circular shape, for example, a nozzle head having a shape corresponding to the cross-sectional shape of the flat cross-section glass filament and having a protrusion and a cutout portion for quenching the molten glass, and by controlling the temperature conditions, flat cross-section glass filaments can be obtained.

[0033] Next, a coating device is used to apply a bundling agent or adhesive, and a bundling shoe is used to bundle 10 to 30,000 flat cross-section glass filaments, and a winder is used to wind them onto a tube at high speed, thereby producing the flat cross-section glass fiber of this embodiment. In addition, in the flat cross-section glass fiber of this embodiment, more than 50% of the glass filaments constituting the flat cross-section glass fiber are the above-mentioned flat cross-section glass filaments, preferably more than 80% of the glass filaments are the above-mentioned flat cross-section glass filaments, more preferably more than 90% of the glass filaments are the above-mentioned flat cross-section glass filaments, and further preferably 100% of the glass filaments are the above-mentioned flat cross-section glass filaments.

[0034] The minor diameter and major diameter of the flat cross-section glass filaments included in the flat cross-section glass fiber of the present embodiment can be adjusted by adjusting the major diameter and minor diameter of the nozzle head, the winding speed, the temperature conditions, etc. For example, by speeding up the winding speed, the minor diameter and major diameter can be reduced, and by slowing down the winding speed, the minor diameter and major diameter can be increased.

[0035] The glass composition of the glass forming the flat cross-section glass fiber of the present embodiment is not particularly limited, and for example, the most commonly used glass composition, the E glass composition, can be used. The E glass composition is a composition containing SiO2 in the range of 52.0 to 56.0 mass %, Al2O3 in the range of 12.0 to 16.0 mass %, MgO and CaO in the range of 20.0 to 25.0 mass %, and B2O3 in the range of 5.0 to 10.0 mass % relative to the total amount of the glass filaments.

[0036] Examples of the flat cross-section glass fiber include glass yarn, glass fiber chopped strands, glass roving, glass powder, and glass fiber mat. In addition, the glass fiber may be in the form of glass cloth composed of glass yarn or glass roving, chopped strand mat composed of glass fiber chopped strands, or in the form of glass filaments dispersed in a glass fiber reinforced resin molded article.

[0037] For example, in the case where the flat cross-section glass fiber of the present embodiment is chopped strands, the number of glass filaments constituting the flat cross-section glass fiber is, for example, 10 to 20,000, preferably 50 to 10,000, and more preferably 1,000 to 8,000. In addition, the length of the chopped strands of the flat cross-section glass fiber of the present embodiment is, for example, 1.0 to 100.0 mm, preferably 1.2 to 51.0 mm, more preferably 1.5 to 30.0 mm, further preferably 2.0 to 15.0 mm, and particularly preferably 2.3 to 7.8 mm. Here, the chopped strands can be obtained by cutting the flat cross-section glass fiber obtained by the above method into a predetermined length using a known device such as a long fiber cutting device. Among them, the long fiber cutting device cuts the glass strands fed between a cutter roller of a cutter (cutting blade) installed radially at equal intervals and a rubber roller that rotates in contact with the cutter roller and is equipped with rubber on the outer circumference.

[0038] When the flat cross-section glass fiber of the present embodiment is a roving, the number of glass filaments constituting the flat cross-section glass fiber is, for example, 200 to 30000. The roving as the flat cross-section glass fiber of the present embodiment has a mass per unit area of ​​35 to 10000 tex (g / km).

[0039] In the case where the flat cross-section glass fiber of the present embodiment is glass powder (sometimes also referred to as cut fiber), the number of glass filaments constituting the flat cross-section glass fiber is, for example, 10 to 20,000. In addition, the length of the glass powder as the flat cross-section glass fiber of the present embodiment is, for example, 0.001 to 0.900 mm. Here, the glass powder can be made in the following manner: the flat cross-section glass fiber made by the above method is crushed into glass powder having the above specified length by a known method such as a ball mill or a Henschel disperser.

[0040] In the flat cross-section glass fiber of the present embodiment, the major axis and the minor axis of the cross section can be measured, for example, as follows.

[0041] First, in the case where the flat cross-section glass fiber of the present embodiment is not contained in the glass fiber reinforced resin molded product, the flat cross-section glass fiber is embedded in a resin such as an epoxy resin and the resin is cured, the cured resin is cut and its cross section is ground, and then the cross section of the cured resin is observed using an electron microscope. Then, for all the flat cross-section glass filaments or more than 200 filaments constituting the flat cross-section glass fiber exposed in the cross section of the cured resin, the longest side passing through the approximate center of the flat cross-section glass filament is taken as the major diameter, and the side orthogonal to the longest side at the approximate center of the flat cross-section glass filament is taken as the minor diameter, and the lengths of the major diameter and the minor diameter of each cross section are measured respectively.

[0042] In addition, when the glass fiber reinforced resin molded product contains the flat cross-section glass fiber, the glass fiber reinforced resin molded product is cut and its cross section is ground, and then the cross section of the resin is observed using an electron microscope. Then, for more than 200 flat cross-section glass filaments constituting the flat cross-section glass fiber exposed from the cross section of the resin, the longest side passing through the approximate center of the flat cross-section glass filament is taken as the major diameter, and the side orthogonal to the longest side at the approximate center of the flat cross-section glass filament is taken as the minor diameter, and the lengths of the major diameter and the minor diameter of each cross section are measured respectively.

[0043] Here, regardless of whether the glass fiber reinforced resin molded product contains the above-mentioned flat cross-section glass filaments or not, the major and minor diameters of the cross section of the above-mentioned flat cross-section glass filaments can be measured by processing the image obtained by an electron microscope using an automatic analysis device.

[0044] In the flat cross-section glass fiber of the present invention, the major diameter of the cross section of the flat cross-section glass filament is in the range of 15.0 to 25.0 μm, preferably in the range of 16.1 to 23.9 μm, and more preferably in the range of 17.1 to 22.4 μm.

[0045] In the flat-section glass fiber of the present invention, the minor axis of the cross-section of the above-mentioned flat-section glass filament is in the range of 8.0 to 12.0 μm, preferably in the range of 8.6 to 11.4 μm, and more preferably in the range of 9.1 to 11.0 μm.

[0046] The above-mentioned profile ratio R can be calculated in the form of the ratio of the major axis to the minor axis (major axis / minor axis) of the above-mentioned cross-section measured by the above method.

[0047] In addition, the area of the rectangle circumscribing the cross-section of the above-mentioned flat-section glass filament can be calculated in the form of the product of the minor axis and the major axis (minor axis × major axis) based on the major axis and minor axis of the above-mentioned cross-section measured by the above method. When measuring the major axis and minor axis of the above-mentioned cross-section, well-known image analysis software such as "A Image-kun" (registered trademark, manufactured by Asahi Kasei Engineering Corporation) can be used to measure the cross-sectional area of the above-mentioned flat-section glass filament.

[0048] And the above-mentioned filling rate P can be calculated in the form of the ratio of the cross-sectional area of the above-mentioned flat-section glass filament to the area of the rectangle circumscribing the cross-section of the above-mentioned flat-section glass filament (cross-sectional area of the flat-section glass filament / area of the rectangle circumscribing the cross-section of the flat-section glass filament).

[0049] In the flat-section glass fiber of the present embodiment, if the above-mentioned profile ratio R exceeds 3.0, the spinnability and the productivity of the chopped filaments decrease. If the above-mentioned profile ratio R is less than 1.5, the glass fiber reinforced resin molded product of the present invention cannot obtain sufficient dimensional stability and mechanical properties such as tensile strength.

[0050] In the flat glass fiber of the present embodiment, the above-mentioned profile ratio R is preferably in the range of 1.6 to 2.8, more preferably in the range of 1.7 to 2.5, and further preferably in the range of 1.8 to 2.3.

[0051] In addition, if the above-mentioned filling rate P of the flat-section glass fiber of the present invention exceeds 89.9%, the cross-sectional shape is too close to a rectangle, so the spinnability and the productivity of the chopped filaments decrease. If the above-mentioned filling rate P is less than 80.1%, the cross-sectional shape is too close to an ellipse, so the glass fiber reinforced resin molded product of the present invention cannot obtain sufficient mechanical properties such as tensile strength.

[0052] In the flat-section glass fiber of the present embodiment, the above-mentioned filling rate P is preferably in the range of 86.4% or less, more preferably in the range of 84.9% or less, further preferably in the range of 80.6 to 84.4%, and particularly preferably in the range of 81.6 to 83.9%.

[0053] In the flat cross-section glass fiber of the present embodiment, it is preferred that each flat cross-section glass filament has a substantially symmetrical cross-sectional shape with respect to the longest side passing through substantially the center of the flat cross-section glass filament.

[0054] In the flat cross-section glass fiber of the present embodiment, although the larger the filling ratio P, the more obvious the effect of improving the tensile strength and warpage, there is a tendency for the spinnability and the short strand manufacturing property to deteriorate. On the other hand, the larger the profile ratio R, the more obvious the effect of improving the tensile strength and warpage, but the spinnability and the short strand manufacturing property become worse. It can be considered that formula (1) represents the balance of the above situation.

[0055] According to the flat cross-section glass fiber of the present embodiment, by making the profile ratio R and the filling rate P satisfy the formula (1), in the glass fiber reinforced resin molded product of the present embodiment containing the flat cross-section glass fiber, the same mechanical properties such as dimensional stability and tensile strength can be maintained as compared with the glass fiber reinforced resin molded product containing the oblong cross-section glass fiber, and compared with the oblong cross-section glass fiber, excellent spinnability and excellent chopped strand productivity can be obtained.

[0056] Here, being able to maintain the same dimensional stability compared to a glass fiber reinforced resin molded product containing oblong cross-section glass fibers means that the warpage of the glass fiber reinforced resin molded product measured by the measuring method described later is less than 10.0 mm. In addition, being able to maintain the same mechanical properties compared to a glass fiber reinforced resin molded product containing oblong cross-section glass fibers means that the tensile strength measured by the measuring method described later is more than 230 MPa.

[0057] In addition, being able to obtain excellent spinnability means that the number of spinning breaks measured by the measurement method described below is less than 10 times. In addition, being able to obtain excellent chopped strand productivity means that the number of blade replacements measured by the measurement method described below is less than 30 times.

[0058] [Measurement method for warpage of glass fiber reinforced resin molded products]

[0059] First, the surface of the flat cross-section glass fiber was coated with a composition containing a silane coupling agent, and the fiber was cut into 3 mm in length to prepare chopped strands. Next, a twin-screw mixer (manufactured by Shibaura Machine Co., Ltd., trade name: TEM-26SS) was used, the screw speed was set to 100 rpm, and the chopped strands and polyamide 6 resin (manufactured by Ube Industries, Ltd., trade name: UBE1015B) were mixed at a temperature of 270° C. to prepare resin pellets having a glass fiber content of 50% by mass.

[0060] Next, the resin pellets were used to perform injection molding using an injection molding machine (manufactured by Nissei Resin Industry Co., Ltd., trade name: NEX80) at a mold temperature of 80°C and an injection temperature of 270°C to obtain a flat plate having a size of 80 mm in length × 60 mm in width × 1 mm in thickness, i.e., a warpage test piece. When one corner of the warpage test piece was brought into contact with a flat surface, a vernier caliper was used to measure the distance between the corner located at a position diagonally opposite to the corner in contact with the flat surface and the flat surface. The distances were measured when the four corners of the warpage test piece were in contact with the flat surface, and the average of the measured values ​​was taken as the warpage value.

[0061] [Method for determining the tensile strength of glass fiber reinforced resin molded products]

[0062] First, the resin pellets were injection molded using an injection molding machine (manufactured by Nissei Plastic Industry Co., Ltd., trade name: NEX80) at a mold temperature of 80° C. and an injection temperature of 270° C. to obtain a type A dumbbell test piece (thickness 4 mm) in accordance with JIS K7165: 2008. A static tensile test was performed using a precision universal testing machine (manufactured by Shimadzu Corporation, trade name: Autograph AG-5000B) at a test temperature of 23° C. in accordance with JIS (Japanese Industrial Standards) K 7165: 2008 to measure the tensile strength of the type A dumbbell test piece.

[0063] [Method for measuring the number of spinning breakages]

[0064] When the flat cross-section glass fiber is manufactured for 30 days, the number of times the flat cross-section glass filaments constituting the flat cross-section glass fiber break during one shift is measured, with one shift being set to 8 hours, and the average number of breaks per shift is taken as the number of spinning breaks.

[0065] [Method for measuring chopped strand productivity]

[0066] The glass strands obtained by coating the surface of the flat cross-section glass fiber with a composition containing a silane coupling agent were cut into 3 mm lengths using a long fiber cutting device, thereby measuring the number of times the cutter was replaced when producing 240 hours of chopped strands, wherein the long fiber cutting device cuts the glass strands between a cutter roller of cutters (cutting blades) radially installed at equal intervals and a rubber roller rotating in contact with the cutter roller and equipped with rubber on the outer peripheral surface.

[0067] In addition, by making the above-mentioned profile ratio R and the above-mentioned filling rate P of the flat cross-section glass fiber of the present embodiment satisfy the above-mentioned formula (2), the glass fiber reinforced molded product of the present invention can obtain excellent mechanical properties such as dimensional stability and tensile strength compared with the glass fiber reinforced resin molded product containing oblong cross-section glass fiber, and the above-mentioned flat cross-section glass fiber can obtain better spinnability than the oblong cross-section glass fiber.

[0068] Here, the ability to obtain excellent dimensional stability compared to a fiber-reinforced resin molded product containing oblong cross-section glass fibers means that the warpage of the glass-reinforced resin molded product measured by the above method is 7.5 mm or less. In addition, the ability to obtain excellent mechanical properties compared to a fiber-reinforced resin molded product containing oblong cross-section glass fibers means that the tensile strength measured by the above method is 240 MPa or more.

[0069] Further, being able to obtain more excellent spinnability means that the number of spinning breaks measured by the above method is less than 9. Further, being able to obtain more excellent chopped strand productivity means that the number of blade replacements measured by the above method is less than 20.

[0070] Next, the glass fiber reinforced resin composition of the present embodiment contains the flat cross-section glass fiber of the present embodiment in a resin composition.

[0071] Next, the glass fiber reinforced resin molded product of this embodiment is composed of the glass fiber reinforced resin composition of this embodiment. The glass fiber reinforced resin molded product of this embodiment can maintain the same mechanical properties such as dimensional stability and tensile strength as glass fiber reinforced resin molded products containing oblong cross-section glass fibers.

[0072] Here, the meaning of being able to maintain the same mechanical properties such as dimensional stability and tensile strength as those of a glass fiber-reinforced resin molded product containing oblong cross-section glass fibers is the same as described above.

[0073] Examples of the resin composition constituting the glass fiber reinforced resin composition of the present embodiment include a resin composition containing a thermoplastic resin or a thermosetting resin.

[0074] Examples of the thermoplastic resin include polyethylene, polypropylene, polystyrene, styrene / maleic anhydride resin, styrene / maleimide resin, polyacrylonitrile, acrylonitrile / styrene (AS) resin, acrylonitrile / butadiene / styrene (ABS) resin, chlorinated polyethylene / acrylonitrile / styrene (ACS) resin, acrylonitrile / ethylene / styrene (AES) resin, acrylonitrile / styrene / methyl acrylate (ASA) resin, styrene / acrylonitrile (SAN) resin, methacrylic resin, polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), polyamide, polyacetal, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polypropylene terephthalate (PPT ... Poly(tert-butylene glycol) (PTT), polycarbonate, polyarylene sulfide, polyethersulfone (PES), polyphenylene sulfone (PPSU), polyphenylene ether (PPE), modified polyphenylene ether (m-PPE), polyarylene ketone, liquid crystal polymer (LCP), fluororesin, polyetherimide (PEI), polyarylate (PAR), polysulfone (PSF), polyamideimide (PAI), polyaminobismaleimide (PABM), thermoplastic polyimide (TPI), polyethylene naphthalate (PEN), ethylene / vinyl acetate (EVA) resin, ionomer (IO) resin, polybutadiene, styrene / butadiene resin, polybutene, polymethylpentene, olefin / vinyl alcohol resin, cyclic olefin resin, cellulose resin, polylactic acid, etc.

[0075] Examples of the polyethylene include high-density polyethylene (HDPE), medium-density polyethylene, low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and ultra-high molecular weight polyethylene.

[0076] Examples of the polypropylene include isotactic polypropylene, syndiotactic polypropylene, atactic polypropylene, and mixtures thereof.

[0077] Examples of the polystyrene include general-purpose polystyrene (GPPS) which is atactic polystyrene having an atactic structure, high impact polystyrene (HIPS) obtained by adding a rubber component to GPPS, and atactic polystyrene having an atactic structure.

[0078] Examples of the methacrylic resin include polymers obtained by homopolymerizing one methacrylic resin selected from acrylic acid, methacrylic acid, styrene, methyl acrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, and fatty acid vinyl esters, and polymers obtained by copolymerizing two or more of the methacrylic resins.

[0079] Examples of the polyvinyl chloride include homopolymers of vinyl chloride polymerized by conventionally known methods such as emulsion polymerization, suspension polymerization, microsuspension polymerization, and bulk polymerization, copolymers of monomers copolymerizable with vinyl chloride monomers, and graft copolymers in which vinyl chloride monomers are graft-polymerized onto polymers.

[0080] Examples of the polyamide include polycaprolactam (polyamide 6), polyhexamethylene adipamide (polyamide 66), polybutylene adipamide (polyamide 46), polybutylene sebacamide (polyamide 410), polyadipamide (polyamide 56), polysebacamide (polyamide 510), polysebacamide (polyamide 610), polydodecanoyl diamine (polyamide 612), polyadipamide (polyamide 106), polydecanediamine (polyamide 1010), polydecanediamine (polyamide 1012), polyhexamethylene adipamide (polyamide 10 ...6). 1,2-dimethylbenzene adipamide (polyamide 1012), polyundecanamide (polyamide 11), polyundecanamide (polyamide 116), polydodecaneamide (polyamide 12), polyxylene adipamide (polyamide XD6), polyxylene adipamide (polyamide XD10), polym-phenylene adipamide (polyamide MXD6), polyp-phenylene adipamide (polyamide PXD6), polybutylene terephthalamide (polyamide 4T), polypentamethylene terephthalamide (polyamide Polyamide 5T), polyhexamethylene terephthalamide (polyamide 6T), polyhexamethylene isophthalamide (polyamide 6I), polynonane terephthalamide (polyamide 9T), polydecane terephthalamide (polyamide 10T), polyundecanediamine terephthalamide (polyamide 11T), polydodecane terephthalamide (polyamide 12T), polybutylene isophthalamide (polyamide 4I), polybis(3-methyl-4-aminohexyl)methane terephthalamide (polyamide PAC MT), polybis(3-methyl-4-aminohexyl)methane isophthalamide (polyamide PACMI), polybis(3-methyl-4-aminohexyl)methane dodecanamide (polyamide PACM12), polybis(3-methyl-4-aminohexyl)methane myristamide (3-methyl-4-aminohexyl)methane myristamide (polyamide PACM14), or a copolymer composed of two or more components, and a mixture thereof.

[0081] Examples of the polyacetal include a homopolymer having an oxymethylene unit as a main repeating unit and a copolymer mainly composed of an oxymethylene unit and containing an oxyalkylene unit having 2 to 8 adjacent carbon atoms in the main chain.

[0082] Examples of the polyethylene terephthalate include polymers obtained by polycondensing terephthalic acid or a derivative thereof with ethylene glycol.

[0083] Examples of the polybutylene terephthalate include polymers obtained by polycondensing terephthalic acid or a derivative thereof with 1,4-butanediol, and the like.

[0084] Examples of the polytrimethylene terephthalate include polymers obtained by polycondensing terephthalic acid or a derivative thereof with 1,3-propylene glycol, and the like.

[0085] Examples of the polycarbonate include polymers obtained by an ester exchange method in which a dihydroxydiaryl compound is reacted with a carbonate such as diphenyl carbonate in a molten state, and polymers obtained by a phosgene method in which a dihydroxydiaryl compound is reacted with phosgene.

[0086] Examples of the polyarylene sulfide include linear polyphenylene sulfide, cross-linked polyphenylene sulfide that has a high molecular weight by a curing reaction after polymerization, polyphenylene sulfide sulfone, polyphenylene sulfide ether, and polyphenylene sulfide ketone.

[0087] Examples of the modified polyphenylene ether include polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and polystyrene, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / butadiene copolymers, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / maleic anhydride copolymers, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and polyamides, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / butadiene / acrylonitrile copolymers, and the like.

[0088] Examples of the polyaryletherketone include polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), and polyetheretherketoneketone (PEEKK).

[0089] As the above-mentioned liquid crystal polymer (LCP), there can be mentioned (co)polymers composed of one or more structural units selected from aromatic hydroxycarbonyl units, aromatic dihydroxy units, aromatic dicarbonyl units, aliphatic dihydroxy units, aliphatic dicarbonyl units, etc. which are thermotropic liquid crystal polyesters.

[0090] Examples of the fluororesins include polytetrafluoroethylene (PTFE), perfluoroalkoxy resin (PFA), fluorinated ethylene propylene resin (FEP), fluorinated ethylene tetrafluoroethylene resin (ETFE), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), and ethylene / chlorotrifluoroethylene resin (ECTFE).

[0091] Examples of the ionomer (IO) resin include copolymers of olefins or styrene and unsaturated carboxylic acids, wherein a part of the carboxyl groups are neutralized with metal ions.

[0092] Examples of the olefin / vinyl alcohol resin include ethylene / vinyl alcohol copolymers, propylene / vinyl alcohol copolymers, ethylene / vinyl acetate copolymer saponified products, and propylene / vinyl acetate copolymer saponified products.

[0093] Examples of the cyclic olefin resin include monocyclic compounds such as cyclohexene, polycyclic compounds such as tetracyclopentadiene, and polymers of cyclic olefin monomers.

[0094] Examples of the polylactic acid include poly-L-lactic acid which is an L-isomer homopolymer, poly-D-lactic acid which is a D-isomer homopolymer, and stereocomplex polylactic acid which is a mixture thereof.

[0095] Examples of the cellulose resin include methyl cellulose, ethyl cellulose, hydroxy cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, cellulose acetate, cellulose propionate, and cellulose butyrate.

[0096] In addition, examples of the above-mentioned thermosetting resins include: unsaturated polyester resins, vinyl ester resins, epoxy (EP) resins, melamine (MF) resins, phenolic resins (PF), polyurethane resins (PU), polyisocyanates, polyisocyanurates, polyimides (PI), urea-formaldehyde (UF) resins, silicone (SI) resins, furan (FR) resins, benzoguanamine (BR) resins, alkyd resins, xylene resins, bismaleimide triazine (BT) resins, diallyl phthalate resins (PDAP), and the like.

[0097] It should be noted that, in the flat cross-section glass fiber of the present embodiment, the flat cross-section glass filaments constituting the above-mentioned flat cross-section glass fiber may contact each other or may be separated from each other. When the above-mentioned flat cross-section glass filaments are separated from each other, a surface treatment agent or a resin composition constituting a glass fiber reinforced resin molded product may be present between the flat cross-section glass filaments.

[0098] Examples of the surface treatment agent include polyurethane resins, epoxy resins, vinyl acetate resins, acrylic resins, modified polypropylene, especially carboxylic acid-modified polypropylene, (poly)carboxylic acids, especially copolymers of maleic acid and unsaturated monomers, and silane coupling agents.

[0099] In addition, the flat cross-section glass fiber of the present embodiment may be coated with a composition including a lubricant, a surfactant, etc., in addition to being coated with these resins or silane coupling agents. The composition coats the flat cross-section glass fiber at a ratio of 0.1 to 2.0 mass % based on the mass of the flat cross-section glass fiber in a state not coated with the composition.

[0100] It should be noted that the coating of the flat cross-section glass fiber with an organic substance can be implemented in the following manner: for example, in the manufacturing process of the flat cross-section glass fiber, the above-mentioned sizing agent or adhesive containing the above-mentioned resin, the above-mentioned silane coupling agent or the above-mentioned composition solution is applied to the flat cross-section glass fiber using a known method such as a roller coater, and then the flat cross-section glass fiber coated with the above-mentioned resin, the above-mentioned silane coupling agent or the above-mentioned composition solution is dried.

[0101] Here, examples of the silane coupling agent include aminosilane, chlorosilane, epoxysilane, mercaptosilane, vinylsilane, acrylic silane and cationic silane. The silane coupling agent may be used alone or in combination of two or more thereof.

[0102] Examples of the aminosilane include γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-N′-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-anilinopropyltrimethoxysilane.

[0103] Examples of the chlorosilane include γ-chloropropyltrimethoxysilane and the like.

[0104] Examples of the epoxysilane include γ-glycidoxypropyltrimethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

[0105] Examples of the mercaptosilane include γ-mercaptotrimethoxysilane and the like.

[0106] Examples of the vinyl silane include vinyltrimethoxysilane and N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane.

[0107] Examples of the acrylic silane include γ-methacryloxypropyltrimethoxysilane and the like.

[0108] Examples of the cationic silane include N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride and N-phenyl-3-aminopropyltrimethoxysilane hydrochloride.

[0109] Examples of lubricants include modified silicone oils, animal oils and their hydrides, vegetable oils and their hydrides, animal waxes, vegetable waxes, mineral waxes, condensates of higher saturated fatty acids and higher saturated alcohols, polyethylene imine, polyalkyl polyamine alkylamide derivatives, fatty acid amides, and quaternary ammonium salts. The above lubricants may be used alone or in combination of two or more.

[0110] Examples of animal oils include beef tallow and the like.

[0111] Examples of the vegetable oil include soybean oil, coconut oil, rapeseed oil, palm oil, and castor oil.

[0112] Examples of the animal wax include beeswax and lanolin.

[0113] Examples of the vegetable wax include candelilla wax and carnauba wax.

[0114] Examples of the mineral wax include paraffin wax and montan wax.

[0115] Examples of the condensate of a higher saturated fatty acid and a higher saturated alcohol include stearic acid esters such as lauryl stearate.

[0116] Examples of the fatty acid amide include dehydration condensates of polyethylene polyamines such as diethylenetriamine, triethylenetetramine, and tetraethylenepentamine, and fatty acids such as lauric acid, myristic acid, palmitic acid, and stearic acid.

[0117] Examples of the quaternary ammonium salt include alkyltrimethylammonium salts such as lauryltrimethylammonium chloride.

[0118] Examples of the surfactant include nonionic surfactants, cationic surfactants, anionic surfactants, and amphoteric surfactants. The surfactants may be used alone or in combination of two or more.

[0119] Examples of the nonionic surfactant include ethylene oxide propylene oxide alkyl ethers, polyoxyethylene alkyl ethers, polyoxyethylene-polyoxypropylene-block copolymers, alkyl polyoxyethylene-polyoxypropylene-block copolymer ethers, polyoxyethylene fatty acid esters, polyoxyethylene fatty acid monoesters, polyoxyethylene fatty acid diesters, polyoxyethylene sorbitan fatty acid esters, glycerol fatty acid ester ethylene oxide adducts, polyoxyethylene stearyl ethers, hydrogenated castor oil ethylene oxide adducts, alkylamine ethylene oxide adducts, fatty acid amide ethylene oxide adducts, glycerol fatty acid esters, polyglycerol fatty acid esters, pentaerythritol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyol alkyl ethers, fatty acid alkanolamides, acetylene glycols, acetylene alcohols, ethylene oxide adducts of acetylene glycols, and ethylene oxide adducts of acetylene alcohols.

[0120] Examples of the cationic surfactant include alkyldimethylbenzylammonium chloride, alkyltrimethylammonium chloride, alkyldimethylethylammonium ethylsulfate, higher alkylamine acetates, higher alkylamine hydrochlorides, ethylene oxide adducts of higher alkylamines, condensates of higher fatty acids and polyalkylene polyamines, salts of esters of higher fatty acids and alkanolamines, salts of higher fatty acid amides, imidazoline-type cationic surfactants, and alkylpyridinium salts.

[0121] Examples of the anionic surfactant include higher alcohol sulfates, higher alkyl ether sulfates, α-olefin sulfates, alkylbenzene sulfonates, α-olefin sulfonates, reaction products of fatty acid halides and N-methyltaurine, dialkyl sulfosuccinates, higher alcohol phosphates, and phosphates of higher alcohol ethylene oxide adducts.

[0122] Examples of the amphoteric surfactant include amino acid-type amphoteric surfactants such as alkylaminopropionic acid alkali metal salts, and betaine-type and imidazoline-type amphoteric surfactants such as alkyldimethylbetaine.

[0123] As a molding method for obtaining the glass fiber reinforced resin molded product of the present embodiment, for example, there can be mentioned: injection molding, injection compression molding, two-color molding, hollow molding, foam molding (including foam molding using supercritical fluid), insert molding, in-mold coating molding, extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, press molding, blow molding, stamping, infusion, hand lay-up, spraying, resin transfer molding, sheet molding compound molding, bulk molding compound molding, pultrusion molding, filament winding, etc. Among these methods, injection molding is preferred because of its excellent manufacturing efficiency.

[0124] Next, examples of the present invention and comparative examples are shown.

[0125] Example

[0126] [Examples 1 to 4, Comparative Examples 1 to 4, Reference Example 1]

[0127] First, glass raw materials (batch glass) prepared in a manner to have an E glass composition were supplied to a melting furnace, melted at a temperature in the range of 1450 to 1550° C., and the obtained molten glass was pulled out from a sleeve having 200 nozzle heads to obtain a plurality of flat cross-section glass filaments having a minor diameter, a major diameter, a profile ratio R, and a filling rate P shown in Table 1, and the plurality of flat cross-section glass filaments were bundled to obtain flat cross-section glass fibers. At this time, the nozzle head had a hole portion and a wall portion, the hole portion had a flat cross-sectional shape having a major diameter of a predetermined length and a minor diameter of a predetermined length, the wall portion had a cutout portion for cooling the molten glass, the length of the minor diameter of the hole portion was adjusted to a range of 0.2 to 2.5 mm, the ratio of the length of the major diameter of the hole portion to the length of the minor diameter was adjusted to a range of 2.0 to 6.5, and the amount of molten glass passing through each of the nozzle heads was adjusted to a range of 0.1 to 3.0 g / min, thereby obtaining the flat cross-section glass fibers of Examples 1 to 4 and Comparative Examples 1 to 4. It should be noted that the flat cross-section glass filaments of Comparative Example 4 are oval cross-section glass filaments having an oval cross-section shape, and the flat cross-section glass fibers of Comparative Example 4 are oval cross-section glass fibers including a plurality of oval cross-section glass filaments.

[0128] Furthermore, the circular cross-sectional glass fiber of Reference Example 1 was obtained by providing the nozzle head with a hole portion having a true circular cross-sectional shape.

[0129] Next, the number of spinning breakages of the flat cross-section glass fibers of Examples 1 to 4 and Comparative Examples 1 to 4 and the round cross-section glass fiber of Reference Example 1 was measured by the following method, and the chopped strand productivity of each of the glass fibers was determined. The results are shown in Table 1.

[0130] [Determination of the number of spinning breaks]

[0131] After 30 days of manufacturing the flat cross-section glass fibers of Examples 1 to 4 and Comparative Examples 1 to 4 and the circular cross-section glass fibers of Reference Example 1, the number of breaks that occurred in the flat cross-section glass filaments constituting the flat cross-section glass fibers of Examples 1 to 4 and Comparative Examples 1 to 4, or the circular cross-section glass filaments constituting the circular cross-section glass fibers of Reference Example 1 was measured. A shift is set to 8 hours, and the average number of breaks per shift is taken as the number of spinning breaks. The case where the number of spinning breaks per shift is less than 9 times is judged as "A", the case where the number of spinning breaks per shift is 9 times or more and less than 10 times is judged as "B", and the case where the number of spinning breaks per shift is 10 times or more is judged as "C".

[0132] [Determination of chopped strand productivity]

[0133] The surface of each flat cross-section glass fiber of Examples 1 to 4, Comparative Examples 1 to 4, and the surface of the round cross-section glass fiber of Reference Example 1 were coated with a composition containing a silane coupling agent to obtain glass strands, and the glass strands were cut into a length of 3 mm by a long fiber cutting device. The number of times the cutter was replaced was measured 240 hours after the chopped strands were manufactured, and the glass strands with less than 20 changes were judged as "A", the glass strands with more than 20 changes and less than 30 changes were judged as "B", and the glass strands with more than 30 changes were judged as "C". The long fiber cutting device is a device that cuts the glass strands between a cutter roller fed to a cutter (cutting blade) radially installed at equal intervals and a rubber roller rotating in contact with the cutter roller and equipped with rubber on the outer peripheral surface.

[0134] Next, each flat cross-section glass fiber of Examples 1 to 4 and Comparative Examples 1 to 4 and the round cross-section glass fiber of Reference Example 1 was coated with a composition containing a silane coupling agent, and each coated glass fiber was cut into a length of 3 mm to obtain chopped strands of Examples 1 to 4, Comparative Examples 1 to 4 and Reference Example 1. Next, each chopped strand and a polyamide 6 resin (Ube Industries, Ltd., trade name: UBE1015B) were kneaded at a temperature of 270° C. using a twin-screw kneader (manufactured by Shibaura Machine Co., Ltd., trade name: TEM-26SS) with the screw speed set to 100 rpm to prepare resin pellets of Examples 1 to 4, Comparative Examples 1 to 4 and Reference Example 1 having a glass fiber content of 50% by mass.

[0135] Next, each resin pellet was injection molded using an injection molding machine (manufactured by Nissei Plastic Industry Co., Ltd., trade name: NEX80) at a mold temperature of 80°C and an injection temperature of 270°C to obtain a flat plate having a size of 80 mm in length × 60 mm in width × 1 mm in thickness, i.e., a test piece for warpage measurement, and an A-type dumbbell test piece (thickness 4 mm) in accordance with JIS K 7165:2008.

[0136] Next, the warpage of each warpage measurement test piece of Examples 1 to 4, Comparative Examples 1 to 4, and Reference Example 1 was measured by the following measurement method. In addition, the tensile strength of each A-type dumbbell test piece of Examples 1 to 4, Comparative Examples 1 to 4, and Reference Example 1 was measured by the following measurement method. The results are shown in Table 1.

[0137] 〔Measurement of warpage〕

[0138] When one corner of the warpage test piece is brought into contact with a flat surface, the distance between the corner located at a diagonal position with the corner in contact with the flat surface and the flat surface is measured with a vernier caliper. The distances are measured when the four corners of the warpage test piece are in contact with the flat surface, and the case where the average value of the measured values ​​is 7.5 mm or less is evaluated as "A", the case where the average value exceeds 7.5 mm and is less than 10.0 mm is evaluated as "B", and the case where the average value exceeds 10.0 mm is evaluated as "C".

[0139] [Determination of tensile strength]

[0140] The tensile strength of the above-mentioned A-type dumbbell test piece was measured by a static tensile test using a precision universal testing machine (manufactured by Shimadzu Corporation, trade name: Autograph AG-5000B) at a test temperature of 23°C in accordance with JIS K 7165: 2008. A-type dumbbell test pieces with a tensile strength of 240 MPa or more were evaluated as "A", A-type dumbbell test pieces with a tensile strength of 230 MPa or more and less than 240 MPa were evaluated as "B", and A-type dumbbell test pieces with a tensile strength of less than 230 MPa were evaluated as "C".

[0141] [Table 1]

[0142] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Reference Example 1 Short diameter(μm) 10.0 9.7 10.1 9.7 9.6 9.3 10.5 10.0 11.0 Long diameter (μm) 20.0 20.3 19.6 20.4 20.5 24.1 17.5 20.0 11.0 Profile Ratio 2.00 2.09 1.94 2.10 2.14 2.59 1.67 2.00 1.00 Filling rate P(%) 82.8 87.0 87.3 81.0 78.5 81.0 83.6 89.3 78.5 <![CDATA[p 3 / 2 / R]]> 376.7 388.3 420.5 347.1 325.0 281.5 457.7 421.9 695.5 Tensile Strength A A A B C A C A C Warping A A A B C A c A C Spinning break times A A B A A C A C A Chopped Strand Productivity A B B A A A A C A

[0143] It is obvious from Table 1 that the flat cross-section glass fibers of Examples 1 to 4, compared with the oblong cross-section glass fibers of Comparative Example 4, have excellent spinnability (number of spinning breaks) and chopped strand productivity while maintaining the same dimensional stability (warpage) and mechanical properties (tensile strength).

[0144] On the other hand, according to the flat cross-section glass fiber of Comparison Example 1 in which the filling rate P is less than 80.1% and the profile ratio R and the filling rate P do not satisfy the above formula (1) (less than 337.6), it is obvious that the dimensional stability (warping) and mechanical properties (tensile strength) when it is made into a glass fiber reinforced resin molded product are poor. According to the flat cross-section glass fibers of Comparison Examples 2 and 3 in which the profile ratio R and the filling rate P do not satisfy the above formula (1) (greater than 421.2 or less than 337.6), it is obvious that the dimensional stability (warping) or the spinnability (number of spinning breakages) when they are made into glass fiber reinforced resin molded products are poor.

Claims

1. A flat cross-section glass fiber, characterized in that: The invention comprises a plurality of flat cross-section glass filaments having a flat cross-section shape, wherein the cross-section of the flat cross-section glass filaments has a major diameter in the range of 15.0 to 25.0 μm, a minor diameter in the range of 8.0 to 12.0 μm, and a ratio of the major diameter to the minor diameter (major diameter / minor diameter), i.e., a profile ratio R in the range of 1.5 to 3.

0. The ratio of the cross-sectional area of ​​the flat cross-sectional glass filament to the area of ​​the rectangle circumscribed to the cross-sectional area of ​​the flat cross-sectional glass filament (cross-sectional area of ​​the flat cross-sectional glass filament / area of ​​the rectangle circumscribed to the cross-sectional area of ​​the flat cross-sectional glass filament), i.e., the filling rate P, is in the range of 80.1 to 87.3%, and the profile ratio R and the filling rate P satisfy the following formula (1): 337.6≤P 3 / 2 / R≤421.2…(1)。 2. The flat cross-section glass fiber according to claim 1, characterized in that: The profile ratio R and the filling rate P satisfy the following formula (2): 361.9≤P 3 / 2 / R≤382.5…(2)。 3. A glass fiber reinforced resin composition, characterized in that: The flat cross-section glass fiber according to claim 1 or 2 is contained in a resin composition.

4. A glass fiber reinforced resin molded product, characterized in that: The glass fiber reinforced resin composition according to claim 3.

Citation Information

Patent Citations

  • Glass fiber-reinforced resin molded article

    WO2020137004A1

  • Glass fiber-reinforced resin molded article

    CN112469784A